Diagnostic and prognostic value of microRNAs for Alzheimer’s disease: a comprehensive meta-analysis - Cătană, Cristina-Sorina; Crișan, Cătălina-Angela; Opre, Dana; Berindan-Neagoe, Ioana (Medicine and Pharmacy Reports, 2020)
Background and aims. Recent research has shown that microRNAs (miRNAs), a class of sequences regulating gene expression without undergoing translational processes, have been accepted as novel biomarkers of diseases. In the present meta-analysis, our main objective was to evaluate the diagnostic value of miRNAs expressed in different body fluids for AD, more exactly to analyze the discriminative value of miRNAs between AD and control subjects. Methods. Medline and EMBASE were searched for articles written in English language and because the result reporting modalities were extremely different in the studies included in the analysis, the current article comprises 2 meta-analysis studies, each of them using different statistical indicators. The first meta-analysis reviewed 10 studies, which were required to provide sufficient information to allow the calculation of AUC or Cohen’s d for size effect. We proposed a second meta-analysis, starting from the drawbacks identified in this first approach, which used different statistical indicators (fold change) provided by other studies (8 studies). Results. The present study offers an encouraging role of miRNA families in diagnosing AD. The heterogeneity of miRNA expression between the hippocampus, CSF and peripheral blood, the small sample size of each research study, as well as the different methods for miRNA detection remain the main obstacles in interpreting these results. Conclusions.There is a need (in a future perspective) to establish the right miRNA combinations as potent diagnostic biomarkers for AD.